POTENTIAL FISHERY SECTOR TO THE WELFARE OF THE COMMUNITY IN THE PERSPECTIVE OF MAQASID SYARI'AH: Case Study Of People Around Jobokuto Fish Auction Site In Ujung Batu Village, Jepara City, Central Java - Ahmad Lukman Nugraha; Azizah Zawaj (Al-Qardhu, 2022)
Jepara Regency is located at the northern end of Java Island, astronomically Jepara Regency is located between 50 43 ' 20.67 " to 60 47 ' 25.83 " South Latitude and 1100 9 ' 48.02 " to 1100 58 ' 37.40 " East Longitude. The area of fishing area that can be reached by jepara fishermen on the type of pelagic fish covering an area of 1,555.2 Km2, and demersal fish species covering an area of 1,360.8 Km2. Fishery sector is one of the sectors that the government used as one of the potentials to increase economic growth in local, regional or state scale, in the development of fishery sector includes the development of human resources such as fishermen, infrastructure development of fisheries facilities and infrastructure such as fishing ports , Fish Auction Place (TPI) and so on. There are 12 Fish Auction Places in Jepara Regency, one of the largest TPI in Jepara District is TPI Jobokuto. Welfare is measured not only in terms of economy, but from the perspective of sharia maqashid, namely, hifzh al-din, hifzh al-nafs, hifzh al-aql, hifzh al-nasl, and hifzh al-mal. The purpose of this research is 1) To know the role and function of fish auction place to the welfare of the surrounding community who depend on the place of auction of fish Jobokuto: 2) To know the potential of the fishery sector to the welfare of the community around the Fish Auction Place Jobokuto Village Ujung Batu Jepara District Jepara Regency Central Java prespektif maqashid syari'ah. This research method uses qualitative research method approach, using qualitative descriptive method, with case study model. data collection techniques through observation, interviews, and dokumetasi. Data analysis techniques use data reduction, data presentation, and inference. The results of this study that: 1) researchers found that the role and function of TPI for the surrounding community, has not been fully implemented properly and still lacks efficiency in its implementation; 2) The concept of Maqashid Syari'ah has not been fully accepted by the individual community around TPI Jobokuto in Ujung Batu.